An Immunological Non-responder Human Immunodeficiency Virus/Hepatitis C Virus Coinfected Patient: Considerations About a Clinical Case - Correia, Rui (2023)
Human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections are two chronic viral infections that share the same mode of transmission, making HIV/HCV coinfection frequent. Highly active antiretroviral therapy (HAART) was a turning point in HIV treatment and has been shown to successfully restore immune function and reduce the frequency of opportunistic infections. Despite a virological response to HAART, a proportion of patients fail to achieve substantial immune recovery, as measured by peripheral CD4 cell counts. Herein, we present the case of a patient with HIV/HCV coinfection who did not achieve successful immune function restoration despite HIV suppression and HCV treatment. Our goal is to promote discussion. Despite considerable advances in the understanding of the impact of HCV on HIV disease progression, there are many individual variables that influence a patient's immune function. In addition, we consider hypogammaglobulinemia as a possible contributor. Further understanding and improvement of immune reconstitution in patients infected with HIV remain an important field of scientific research.